Pengaruh Penerapan SOP Dan Budaya Kerja Terhadap Produktivitas Kerja Karyawan Line Shock Absorber Assembly PT Kayaba Indonesia - Jon Edy; Soedjatmoko Soedjatmoko (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to determine the effect of applying SOP (standard operating procedures) and work culture on the work productivity of PT Kayaba Indonesia line shock absorber assembly employees. The research method used is a quantitative descriptive approach. The sample of this research is 98 employees of PT Kayaba. The sampling technique is purposive sampling. Using multiple linear regression analysis, classic assumption test and hypothesis testing, namely the t test and F test. The results of the hypothesis test show that the application of SOP has no effect and work culture has an effect on work productivity. The results of the regression analysis showed that the implementation of SOP partially had no effect on work productivity, namely 0.075, work culture partially had an effect of 0.261. The results of the simultaneous hypothesis of the application of SOP and work culture together have a significant effect on work productivity with a coefficient of determination (R2) of 0.073 or 7.3%.